Pemberdayaan Masyarakat Dalam Peningkatan Dan Pemeliharaan Irigasi Di Desa Lupia Kecamatan Kabangka Kabupaten Muna - Ahmad Syarif Sukri; La Welendo; Maskur Kimsan; Nasrul Nasrul; Fitriah Fitriah; Ridwan Syah Nuhun; Baso Mursidi; Adris A. Putra; Siti Nurjanah Ahmad (Vokasi Universitas Halu Oleo, 2022)
The Lupia Village irrigation network was formed in 1981 through farmer groups from the results of non-governmental organizations. Currently the government has given attention and assistance both through the village fund budget and central government funding assistance, however, there is still a need for program sustainability from related parties. The results of the identification were carried out, namely that there were still few people who did not understand about the more effective use of irrigation water, so that there was always a crop failure where other plots of rice fields had excess water while the farthest plots did not get water. The area of land used by the community is currently around + 35 hectares, but the available land and the potential to be used as rice fields are around + 90 hectares, so that what has not been functioned as rice fields is about + 55 hectares. Seeing this condition, it is very potential to be developed to be able to increase the production of rice fields in Lupia Village, from this potential, the Lecturer of the Faculty of Engineering, Halu Oleo University as part of the Tridarma of Higher Education, carries out community service activities through the transfer of knowledge so that the community can develop, increase production, and improve community welfare, especially the residents of Lupia Village, Kabangka District, Muna Regency. The methods used are socialization, technical guidance, training on procedures for implementing technical irrigation canal development so that water is not wasted and can be fully utilized by farming communities. The expected result is that the community can increase the yield of lowland rice production. Seeing the potential of Lupia Village in Kabangka District, it is hoped that the program can be carried out continuously so that it can increase income and a better standard of living for its people.